Hypertension gymnastics as a non-pharmacological intervention in lowering blood pressure - Hairul Ahmad; Nor Isna Tauhidah; Dewi Kartika Wulandari; Pauria; Rusadi; Hafizatul Auliya Az Zahrah; Mahdiyina Sesariani (Abdimas Polsaka, 2025)
Hypertension is a global health issue with a high prevalence, including in Indonesia. South Kalimantan has the highest rate at 44.1% among adults aged ≥18 and above. Most individuals with hypertension remain undiagnosed and untreated. Non-pharmacological interventions, such as hypertension exercise (senam hipertensi), effectively reduce blood pressure through relaxation and improved circulation. This community service program aimed to raise awareness and lower blood pressure among Anjir Serapat Muara 1 Village residents through health screening and hypertension exercise. The methods included an initial health survey, blood pressure measurements before and after the intervention, and several sessions of hypertension exercise. A total of 22 female participants were involved in this activity. Results showed that most participants experienced decreased blood pressure after the intervention. For instance, Mrs. S's blood pressure decreased from 159/103 mmHg to 148/100 mmHg, and Mrs. A's from 149/96 mmHg to 126/81 mmHg. Participants also showed high enthusiasm for the activity. In conclusion, the community well-accepted hypertension exercise as a non-pharmacological approach and effectively helps reduce blood pressure, demonstrating potential for sustainable implementation at the community level